Strategije razvoja mest med evropeizacijo, državo in regijo - Sitar, Metka (Urbani izziv, 2005)
In European and national strategic documents, even Slovene ones, emphasis in physical and regional development, which is aligned to principles of sustainable development, is on goals and directions for balanced spatial development, while contemporary urbanisation processes, conditioned by global competitiveness of the post-industrial age, underline the leading role of large urban centres. On the other hand structural transformations in Europe are increasingly changing spatial relations between states, regions, cities and agglomerations. With growth of economic and infrastructure flows and strategic enforcement of transnational authority a uniform European economic and social space is emerging, in which different integrations are substituting the role of states. We are deliberating on the necessity of changing the viewpoint on prospective development of cities and urban regions, whereby focus of spatial policies and strategies is on integral dealings with space. Conditions for successful, competitive urban economy can be established only by connecting economic policies with other spatially-relevant departmental policies (transport, environment, agriculture etc.); with general welfare as the goal, another component is becoming significantly closer, which is social cohesion. In different chapters the article presents various global, regional and local factors and in European circumstances identifies the most typical factors affecting roles and functions in city development. Starting from various theoretical embarkation points and selected practical examples from different urban environments, the article tries to define possibilities for identifying initiatives and recommendations for designing development policies and strategies that are essential even in Slovene circumstances.
Keywords: Europe; European Union; Evropa; Evropska unija; mesta; strategija; urbani razvoj; urbani sistemi